2014
DOI: 10.1080/13575279.2013.847057
|View full text |Cite
|
Sign up to set email alerts
|

The Applicability of Two Strengths-based Systemic Psychotherapy Models for Young People Following Type 1 Trauma

Abstract: This paper will consider the inter-relationship of a number of overlapping disciplinary theoretical concepts relevant to a strengths-based orientation, including well-being, salutogenesis, sense of coherence, quality of life and resilience. Psychological trauma will be referenced and the current evidence base for interventions with children and young people outlined and critiqued. The relational impact of trauma on family relationships is emphasised, providing a rationale for systemic psychotherapeutic interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…En cuanto al elemento centrado en soluciones, Eads y Lee (2019) revisaron cinco estudios concluyendo que existía un aumento en los niveles de crecimiento postraumático de las personas que recibieron tratamiento desde la TBCS para la superación del trauma. Estos resultados llevan a pensar que este enfoque basado en fortalezas presenta incipiente evidencia de efectividad para el crecimiento postraumático, toda vez que altera la relación de la persona con la experiencia traumática y, por lo tanto, promueve la adaptación, la integración y la recuperación (Coulter, 2014). Zhang et al (2014) llevaron a cabo un estudio cuasi-experimental que tuvo como objetivo evaluar el impacto de una aplicación grupal de TBCS en 43 madres con un hijo con trastorno del espectro autista.…”
Section: La Intervención Tras Eventos Altamente Estresantesunclassified
“…En cuanto al elemento centrado en soluciones, Eads y Lee (2019) revisaron cinco estudios concluyendo que existía un aumento en los niveles de crecimiento postraumático de las personas que recibieron tratamiento desde la TBCS para la superación del trauma. Estos resultados llevan a pensar que este enfoque basado en fortalezas presenta incipiente evidencia de efectividad para el crecimiento postraumático, toda vez que altera la relación de la persona con la experiencia traumática y, por lo tanto, promueve la adaptación, la integración y la recuperación (Coulter, 2014). Zhang et al (2014) llevaron a cabo un estudio cuasi-experimental que tuvo como objetivo evaluar el impacto de una aplicación grupal de TBCS en 43 madres con un hijo con trastorno del espectro autista.…”
Section: La Intervención Tras Eventos Altamente Estresantesunclassified
“…Similar to the use of photography, art, music, storytelling, reconnecting with nature, and metaphor in the Maung et al (2021) study, in the MPM, we have found effective interventions to include a wide range of strategies that can be employed in a culturally responsive manner, including critical incident stress debriefing, cognitive restructuring therapy, metaphor, psychological first aid, role playing, storytelling, dream work, narrative therapy, existential psychotherapy, psychodrama, projective drawing, mythology, critical incident stress management, trauma-focused cognitive-behavioral therapy, relaxation techniques, gestalt therapy, imagery, play therapy, and interpersonal group therapy (Bemak & Chung, 2016, 2017aDuarté-Vélez et al, 2010;Parthasarthi et al, 2004;Schottelkorb et al, 2012). It is important to point out that these intervention strategies are underscored by strength-based approaches that focus on resiliency, especially given refugees' history of trauma and loss compounded by the designation of refugee status (Coulter, 2014;Hughes, 2014;Smith, 2006b). Strengths emerged in the findings of the three studies in this Major Contribution, noting growth in personal development, coping skills, stronger interdependent relationships with others, trusting one's instincts, stronger religious and spiritual convictions, taking risks, greater persistence, cultural competency, less fear, and enhanced pride.…”
Section: Phase I: Mental Health Educationmentioning
confidence: 99%
“…Second, the emphasis on small changes-which will reverberate through client systems to become larger change (De Jong & Berg)-may seem more realistic and manageable for trauma survivors than attempting to directly confront their worst trauma. The miracle question may not be appropriate for clients who have experienced severe trauma, as this does involve picturing the trauma completely gone and may be too much for some clients to imagine (Coulter, 2014).…”
Section: Solution-focused Therapy For Traumamentioning
confidence: 99%
“…Systemic group therapy-with a similar orientation to SFT-outperformed a psychoanalytic group for adult survivors of childhood sexual abuse (Lau & Kristensen, 2007), though the treatment effects diminished over time (Elkjaer, Kristensen, Mortensen, Poulsen, & Lau, 2014). With a strong conceptual argument for SFT's applicability to trauma (Bannink, 2008;Coulter, 2014), current application of SFT for trauma treatment (Froerer et al, 2018), and evidence of effectiveness in populations where trauma is likely (Cepukiene & Pakrosnis, 2011;Koob & Love), a review of the evidence for SFT for trauma survivors is warranted.…”
Section: Solution-focused Therapy For Traumamentioning
confidence: 99%